Upaya Meningkatkan Kunjungan Wisatawan Melalui Strategi Packaging And Programming Paket Wisata Di Taman Kakao Cokelat Desa Banjaroya - Ellen Aurelie Basuki; Tonny Hendratono; Nur Widiyanto (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia, 2024)
Banjaroya Village, Kulon Progo Regency has many tourism potentials, one of which is the Chocolate Cocoa Park. As an educational tourist attraction based on agrotourism, the Chocolate Cocoa Park serves several activities offered to tourists related to the cultivation of Cocoa plants and Chocolate production. However, in this case, the Chocolate Cocoa Park has not packaged and programmed the activity services well. The results of the study show that there are several things that need to be fixed in packaging and providing educational package programs at the Chocolate Cocoa Park. The thing that needs to be fixed is the way to package the tour package, it needs to display an itinerary so that tourists feel easy and can manage their time to participate in the activity. Then the programming is by grouping the activities offered according to the focus of each activity so that tourists can choose what focus activities they want to participate in.